In vitro comparison of fracture strength of maxillary incisors with the simulated external root resorption cavities repaired with BioMTA or Biodentine - Tufan Ozasir; Birgul Ozasir; Nagihan Aribal; Derin Bugu Yuzer; Baris Kandemir; Kamran Gulsahi (Journal of Dental Sciences, 2025)
Background/purpose: Treatment of external root resorption is performed by root canal treatment and repair of the resorptive area with biocompatible materials. Our study aimed to compare the fracture strengths of teeth with simulated external resorption repaired with BioMTA or Biodentine. Materials and methods: Sixty extracted human maxillary incisors were used in the study. The root canals were instrumented with Ni–Ti rotary instruments and obturated with single cone technique using corresponding gutta-percha cone and root canal sealer. The teeth were embedded in acrylic blocks. Fifteen of them served as negative control group. Simulated external resorption cavities were opened with burs on the approximal surfaces of the remaining teeth. Fifteen of them were assigned randomly as positive control group. The remaining teeth were randomly divided into two groups, the cavities were filled with BioMTA in one group and with Biodentine in the other group and then subjected to fracture strength test. The force at which fracture occurred was evaluated by analysis of variance at 0.05 significance level. Results: Biodentine showed significantly higher fracture strength than BioMTA. There was no difference between the negative control group and the Biodentine and BioMTA group. The positive control group showed significantly lower values than the other groups. Conclusion: Both Biodentine and BioMTA may be used to repair external root resorption, while Biodentine is more durable.